RANCANG BANGUN CHATBOT UNTUK KONSELING PSIKOLOGIS MAHASISWA STMIK KHARISMA MAKASSAR BERBASIS WHATSAPP - Pontoh, Zaenab; Marlina (STMIK KHARISMA Makassar, 2025)
Mental health issues such as stress, anxiety, and depression are increasingly experienced by university students, yet access to counseling services remains limited due to social stigma, low mental health literacy, and a shortage of counselors. Restricted service hours and concerns over data confidentiality further reduce the utilization of available services. A similar situation occurs at STMIK Kharisma Makassar, where the counseling unit has not been optimally utilized and its role in supporting students mental health has not been fully effective. This study developed Vikha (Virtual Konseling Kharisma), a WhatsApp-based virtual counseling chatbot designed to provide initial psychological support with empathy. Vikha is powered by OpenAI GPT-4 and applies prompt engineering techniques with four types of prompting: Behavior, Knowledge, Follow-up, and Scheduling. Prototype testing demonstrated that Vikha performed according to its design by delivering empathetic and informative responses. Final evaluation was validated by campus psychologists using scenarios representing common student problems to assess response accuracy, relevance of suggestions, and conversation follow-up. The results confirmed that Vikha is feasible, reliable, and ready to support initial counseling services at STMIK Kharisma Makassar, potentially improving access to and effectiveness of mental health services on campus.